The role of artificial intelligence in mobile banking: decoding portuguese consumers’ perceptions and intentions to engage - João M. Lopes; Ilda Massano-Cardoso; Lara Pedrosa (Future Business Journal)
Abstract The rapid expansion of technology, particularly artificial intelligence, has significantly challenged and transformed traditional banking channels. This transformation has led banks to rethink their service delivery models, shifting towards more digital and customer-centric approaches that emphasize convenience and personalization. The aim of this study is to identify and analyze the main factors that impact the behavioral intentions of Portuguese consumers in the use of artificial intelligence in mobile banking applications. To this end, 452 responses were collected from Portuguese consumers, and multiple linear regression was used as the method. The results show that perceived quality of service and security are the main factors of trust, which increases attitudes towards AI and comfort with its use. Relative advantage strongly promotes intentions to use, while perceived need and excessive comfort surprisingly reduce the likelihood of adoption. Finally, intention to use positively influences attitudes towards AI, highlighting the role of involvement in shaping consumer perceptions. This study distinctively combines trust, security, and comfort in the analysis of AI adoption in mobile banking, revealing counter-intuitive effects of perceived need and comfort on usage intentions. It also highlights how engagement with AI services shapes consumer attitudes, providing new insights into the dynamics of technology acceptance.